Wireless energy-aware non-orthogonal multiple access network under full-duplex mode: performance analysis. (3rd May 2020) - Le, Chi-Bao; Do, Dinh-Thuan
An application of simultaneous wireless information and power transfer (SWIPT) is proposed in this paper to employ in non-orthogonal multiple access (NOMA) network. This paper considers impact self-interference due to full-duplex transmission to system performance evaluation of NOMA transmission. In particular, expressions of outage performance are derived in situation of wireless energy harvesting-based relay in cooperative relaying system to help to forward to far NOMA users. As main advantage, NOMA and full-duplex scheme are two architecture deployed to enhance the spectral efficiency. In addition, a power allocation strategy, energy harvesting time and self-interference factor are considered parameters to perform in simulations. The correct of derived formula is presented via Monte Carlo simulation and it is compared with analytical results.